Evaluation of the effect of honey on the healing of tooth extraction wounds in 4- to 9-year-old children - Mokhtari, S; Sanati, I; Abdolahy, Sh; Hosseini, Z (Nigerian journal of clinical practice, 2019)
Objective: The aim of the this study was to evaluate the effect of honey on the healing of tooth extraction wounds in children 4‒9 years of age. Subjects and Methods: In the present randomized clinical trial, 51 patients, 4‒9 years of age were selected randomly. All the subjects required extraction of one deciduous molar tooth. The subjects were randomly assigned to two groups. In group 1, after extraction of the tooth, the dentist used a cotton swab applicator to place a layer of honey on a piece of gauze moistened with normal saline solution (NSS) and placed it on the socket. In group 2, honey was not used; rather, NSS was applied. On days 3 and 7 after tooth extraction, the wound sizes were measured. Results: In both groups, the wound sizes decreased significantly on the third day compared with baseline and on the seventh day compared with the third day (P < 0.05). On the third and seventh days after tooth extraction, wound sizes in the honey group were significantly lower than those in the NSS group (P < 0.05). Conclusion: Honey resulted in a decrease in wound sizes and faster healing after extraction of teeth in children. Therefore, use of honey can be recommended after minor surgeries in the oral cavity.